Validation of using 2-item and 5-item of the Dizziness Handicap Inventory Thai version for screening Benign Paroxysmal Positional Vertigo (BPPV) in Thai population - Teeratamtada, Krittanai (Thai Journal of Otolaryngology Head and Neck Surgery, 2024)
Abstract Objective: To validate the use of total score, 5-item score, and 2-item score of the Thai version of the Dizziness Handicap Inventory (DHI-TH) for screening benign paroxysmal positional vertigo (BPPV) in Thai population. Study Design: A retrospective electronic medical chart review Setting: Tertiary care teaching hospital Patients: A total of 60 electronic medical records of patients who were diagnosed with BPPV at the vestibular clinic were identified during the period from January 2021 to May 2022. The electronic medical records of another 60 patients with other vestibular disorders were also reviewed. Main Outcome Measures: The total score, 2-item score, and 5-item score of the DHI-TH were obtained. Results: The area under the receiver operating characteristic curve (AUC) of the 2-item and 5- item score for predicting BPPV was 0.855 (95% confidence interval: 0.788-0.923) and 0.806 (95% confidence interval: 0.728-0.884), respectively. Using a cut-off value of 6 in the 2-item score had a good sensitivity of 73.33%, specificity of 80% in discriminating BPPV from those without BPPV. For the 5-item score, a cut-off value of 15 had 63.33% sensitivity and 90% specificity in separating BPPV from non-BPPV. Conclusions: Both 5-item and 2-item scores from the DHI-TH are valid for initial BPPV screening. We recommend using 2-item score due to its time efficiency, aligning with comparable sensitivity and specificity observed in the 5-item score. Keywords: Benign paroxysmal positional vertigo—Dizziness—Screening—Dizziness Handicap Inventory